"Why I like history ...": Ciskeian secondary school pupils' attitudes towards history - Atuahene-Sarpong, Boateng Kofi (Rhodes University, Faculty of Education, Department of Education, 1993)
This dissertation was motivated by the decline in percentage of the number of Standard 10 pupils who offered History for the National Senior Certificate (Matriculation) Examination in the Mathole Directorate in the Ciskei from 1987 - 1990. The research revealed that the decrease in the number of pupils doing History in Standard 10 did not indicate loss of interest in the subject. Instead, the multiplicity of new subjects introduced in the school curriculum and some peculiar subject combinations in some schools forced some pupils (reluctantly) to reject History as a school subject. Those who chose to do History in Standard 10 showed their liking for the subject and expressed their interest in it. The study took the form of a survey through the use of questionnaire and informal chats with pupils and teachers on their views about History as a school subject. A questionnaire was designed for pupils offering History in Standard 10 and administered in four of the eight Senior Secondary Schools in the Mathole Directorate in Ciskei. Generally, work on pupils' interest in and attitude towards History as a school subject is very rare. Some of the few available works merely compare pupils' liking for History as opposed to other school subjects and when the response is not favourable; conclude that pupils in Senior Secondary Schools do not enjoy studying History. Pupils' interest in and attitudes towards the subject, the extent of their interest, the causes of their attitude and the internal and external influences on their interest in and attitudes towards the subject were neglected by earlier works, but have been given attention in this study. As a result of very little available work and material, pupils' responses to the questionnaire formed the basis of the material used in this work. A large number of pupils' responses was put in tables according to sex instead of schools. Where applicable, X2 tests were administered to see if there were any appreciable statistically significant differences between the responses of the boys and girls. In most cases where the X2 tests were applied, no statistically difference was noticed. The study showed more boys than girls showing interest in and positive attitudes towards History. The general picture of the study showed a deviation from the view commonly expressed by other studies that pupils in modern Senior Secondary Schools do not like History. As this study revealed, it is not the subject itself that pupils did not like, but the way it is handled by some teachers and lack of teaching aids to concretise events. This leads to the role of Teacher Training Institutions: which must be to produce the versatile, duty-conscious and innovating History teacher to revolutionise History teaching to make History alive to pupils.
Keywords: History -- Study and teaching (Secondary) -- South Africa--Ciskei -- Attitudes; History -- Study and teaching (Secondary) -- South Africa -- Ciskei